Financial Constraints and Corporate Finance: Insights from Nepalese Firms - Silwal, Prem Prasad (Journal of Business and Social Sciences Research, 2024)
The purpose of this study is to investigate how managers navigate the capital market amidst financial constraints. Expanding upon the findings of Graham and Harvey (2001), Campello et al. (2010), and Bancel and Mittoo (2014), we confine our attention to Nepal as a developing nation. Our approach encompasses criteria and delves into the challenges associated with securing financing, utilizing descriptive analysis. The study entailed surveying 198 financial executives using a structured questionnaire. Among the respondents, nearly half of them indicated that they experienced financial issues at a specific point in time. The survey focused on the financing challenges that managers face when considering potential projects for their undertakings. The findings revealed that managers prioritize the use of internal equity, followed by external equity, and lastly, debt. Interestingly, this order contradicts the hierarchical theory. Financially constrained firms identified several major obstacles when raising funds from banks, including high interest rates, lengthy banking processes, and bank fees. Additionally, it has been uncovered that maintaining financial flexibility and considering firm size are crucial factors for the company in addressing their financial shortfall.